Mechanical behavior of hybrid glass Fiber-Jute reinforced with polymer composite for the wall of the Acehnese boat 'Jalo Kayoh' - Akram, A.; Hasanuddin, Iskandar; Nazaruddin, N.; Putra, R.; M. M., Noor (IOP Publishing, 2019)
Hybrid fiber composites are widely used composites in engineering applications, especially for the frame and wall structure of Acehnese traditional boat Jalo Kayoh. The purpose of this study is to obtain a hybrid material which is a blend of natural jute fiber reinforced with the synthetic fibers E-glass and polyester as a matrix. The materials potential to become a material for the structure and walls in the traditional Acehnese boat Jalo Kayoh. The fabrication of the hybrid composites is carried out manually using an engineered press at a pressure of 25 kg/cm2 for 24 hours. The ratio of jute fiber and E-glass in the composites at each layer are (1:0), (1:1) and (2:1). Tensile testing of the hybrid composites refers to ASTM D 3039 - 00. The results show that the tensile strength of the hybrid composites tends to increase with the increase in the volume of the fiber, with the maximum tensile strength of 4.8 MPa. The increasing number of layers in the jute and E-glass is adding strength to the composites. This will be good to use in the initial material of the structure and walls in the traditional Acehnese boat Jalo Kayoh.